A Summary of Research in Science Education 1981 / Burton E. Voss. - Voss, Burton E. (Distributed by ERIC Clearinghouse, 1982)
The review of science education research for 1981 includes individual analyses of approximately 400 dissertation abstracts, journal articles, research reports, and papers presented at conferences. The organization of the review is topical. Topics include: (1) status studies of science education; (2) cognitive style; (3) Piagetian studies; (4) student characteristics, attitudes, and interests; (5) teaching strategies and learning; (6) teacher use of instructional materials and learning; (7) instructional technology; (8) evaluation instrumentation and methodology; (9) curriculum research; (10) teacher education; and (11) science supervision. A rationale is provided at the beginning of each section for the particular studies clustered into it. A summary is provided at the end of each section. It is noted that 1981 was the beginning of publication of many meta-analyses on specific subjects in science education. Since these studies have the potential of "clouding" the summary of findings of a particular year, most of these meta-analyses were placed in the summary of each section. (Author/JN)
ERIC Document Number: ED223464.
Availability: John Wiley & Sons, Inc., 605 Third Ave., New York, NY 10016.
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: 400-78-0004.
Educational level discussed: Elementary Secondary Education.
Keywords: Academic Achievement.; Cognitive Development.; Cognitive Style.; College Science.; Developmental Stages.; Elementary School Science.; Elementary Secondary Education.; Evaluation Methods.; Higher Education.; Instructional Materials.; Learning.; Science Curriculum.; Science Education.; Science Instruction.; Science Supervision.; Secondary School Science.; Student Characteristics.; Teacher Education.; Teaching Methods.